Pengaruh Kualitas Pelayanan, Tampilan Museum dan Manajemen Koleksi Terhadap Kepuasan Wisatawan Monumen Yogya Kembali - Tuti Panghastuti Panghastuti (Media Wisata, 2016)
Museums are more important than ever before. They play a substantial role in people‟s leisure activities and belong to one of the most important tourist attractions. The visitors have a strong effect on local economies, especially in touristic locations. Not surprisingly therefore more and more museums are founded usually in spectacular buildings. This research employs three dimensions of service quality to understand the factors underlying tourist satisfaction of „Monumen Yogya Kembali‟.These dimensions investigated are namely Service Quality, The Appearance of the Museum and Collection Management. Sampling has been conducted at the Monumen Yogya Kembali between October 12- 25th 2015. Convenient random sampling has been employed to 100 respondents. Through a 4 point Likert-type scale, tourists‟ expectations of a perfect service provider have been compared with the practices of Monumen Yogya Kembali to determine if there are any gaps. Service Quality, the Appearance of the Museum, and Collection Management‟ has been analyzed together with its effects on tourist‟ satisfaction through regression analysis. Linear regression analysis is conducted to test the research model. The regressionmodel that explains the satisfaction variable via Service Quality, the Appearance of the Museum, and Collection Management factors is tested. Accordingly, the tested regression model is meaningful (F: 34,651, p < 0.001) and independent variables can explain the50,5% of the change in the satisfaction variable. Closer analysis of the model parameterssuggests Service Quality, the Appearance of the Museum, and Collection Management variables have a significantly positive effect on satisfaction.